Front Cover: Potassium Salts of 2, 5‐Bis(trimethylsilyl)‐Germolide: Switching between Aromatic and Non‐Aromatic States (Chem. Eur. J. 46/2019). Issue 46 (24th July 2019) - Dong, Zhaowen; Schmidtmann, Marc; Müller, Thomas
Abstract : Aromaticity becomes germane, the germanium version of cyclopentadienide (Cp − ) : The potassium salt of a planar aromatic germacyclopentadienide was synthesized by the reduction of a 1‐mesityl‐2, 5‐bis‐trimethylsilylchlorogermole with two equivalents of KC8 . Its solid‐state structure revealed contact ion pairs with the potassium ion η 5 ‐coordinated to the germacyclopentadienide ring. Complexation of the potassium cation with 18‐crown‐6 triggers the structural switch to the non‐planar isomer with a localized structure. This work shows for the first time clear structural evidence for the switch between the delocalized, aromatic form and the localized, diene‐like isomer of a heterole anion triggered by the coordination of an alkali metal cation. More information can be found in the Full Paper by T. Müller et al. onpage 10858 .